Changes in Canine Angulation after Dentoalvelaor Distraction with a Rigid Maxillary Intraoral Distractor: A Radiographic Study (Orthodontic Journal of Nepal, 2013)
Introduction: Prolonged treatment duration is a major problem of orthodontic patients. Canine retraction through dentoalveolar distraction osteogenesis was introduced to reduce the overall orthodontic treatment period. Objective: To evaluate the canine angulation by means of dentoalveolar distraction osteogenesis to achieve rapid canine retraction. Materials & Method: The study sample consisted of 20 maxillary canines in 10 adult patients (mean age 19.53 years). First bicuspids were extracted, a rigid custom made intraoral distractor was placed, distraction osteogenesis surgical procedure was performed. Result: Complete retraction of canines was achieved in a mean duration of 9.23 days with minimal anchorage loss. The mean change in canine angulation was 10.13° ± 3.44°. Bodily movements of the canines were noticed with minimal tipping of mean 7.11° (6°-8° range). No radiographic and clinical complications were encountered. Conclusion: There was a significant change in canine angulation after distraction. DOI: http://dx.doi.org/10.3126/ojn.v3i1.9283 Orthodontic Journal of Nepal, Vol.3, No.1, 2013: 53-57